INDONESIA PARTICIPATION IN DEFENSE DIPLOMACY IN INDO-PACIFIC [PARTISIPASI INDONESIA DI DIPLOMASI PERTAHANAN INDO-PASIFIK] - Jasmine Sika Dewita (Universitas Pelita Harapan, 2021)
Global political, economic, and social dynamics in this modern era have shifted the interests of every nation from defense power acquirement to domination of resources. One of the richest of resources area is Indo-Pacific. There is still no international statute about the region’s territorial borders, but some powerful states compose their own version of the borders scheme, based on their own national interests. As general geographical consensus, the area ranges from Pacific Ocean, Indian Ocean, and the land areas within. The geopolitically strategic region contains plenteous potential to empower Blue Economy and shipping industry, but also appeals various maritime security issues like piracy, smuggling and illegal fishing. Indonesia as one of the Founding Fathers of ASEAN and located at the strategic point of international trade route, has lots of potential to be major player in Indo-Pacific. Indonesia needs to enhance its political role while defending Indo-Pacific security through defense diplomacy. This research is conducted using qualitative method, with literature resources from various books, international articles, government and news website. The result of this research explains about Indonesia participation on defense diplomacy in Indo-Pacific, including the activities, opportunities and challenges within, and Indonesia’s national interest in the defense diplomacy.Bahasa Indonesia Abstract: Dinamika politik, ekonomi, dan sosial global di era modern ini telah menggeser kepentingan setiap bangsa terhadap kekuatan pertahanan menjadi penguasaan sumber daya alam. Salah satu daerah yang kaya akan sumber daya adalah Indo-Pasifik. Masih belum ada undang-undang internasional tentang perbatasan teritorial kawasan, tetapi beberapa negara kuat yang menyusun skema perbatasan versi mereka sendiri, berdasarkan kepentingan nasional mereka sendiri. Sebagai konsensus geografis umum, wilayahnya berkisar dari Samudra Pasifik, Samudra Hindia, dan wilayah daratan di dalamnya. Kawasan yang secara geopolitik strategis ini memiliki potensi besar untuk pemberdayaan Ekonomi Biru atau industri perkapalan dan juga menarik berbagai masalah keamanan maritim seperti pembajakan, penyelundupan, dan penangkapan ikan ilegal. Indonesia sebagai salah satu Founding Fathers ASEAN dan terletak di titik strategis jalur perdagangan internasional, memiliki banyak potensi untuk menjadi pemain utama di Indo-Pasifik. Indonesia perlu meningkatkan peran politiknya sekaligus mempertahankan keamanan Indo-Pasifik melalui diplomasi pertahanan. Penelitian ini dilakukan dengan metode kualitatif, dengan sumber literatur dari berbagai buku, artikel internasional, pemerintah dan situs berita. Hasil penelitian ini menjelaskan tentang partisipasi Indonesia dalam diplomasi pertahanan di Indo-Pasifik, termasuk kegiatan, peluang dan tantangan di dalamnya, serta kepentingan nasional Indonesia dalam diplomasi pertahanan.